OPTIMALISASI PEMANFAATAN TEKNOLOGI DALAM STRATEGI PROMOSI DI MI NURUL HIKMAH - Halimatuzzahrah; Heri Fadli; Eva Zulfa (Global Action and Education for Society, 2025)
This study aims to analyze the use of technology in the promotion strategy at MI Nurul Hikmah and identify the obstacles faced. The method used is qualitative with a case study approach. Data were collected through interviews, observations, and documentation, then analyzed by data reduction, data presentation and conclusion drawing, data validity test using source triangulation and technique triangulation. The results showed that technology, especially social media and websites, has helped madrasah in disseminating information and increasing visibility. However, the utilization of technology in promotion is still partial and not well integrated. The main obstacles faced are the limited competence of human resources, inadequate technology infrastructure, and limited budget. Based on digital transformation theory, the success of technology requires structured planning and professional management. This study recommends MI Nurul Hikmah to develop a more structured promotion strategy, including digital training for staff, professional management of social media and website, and improvement of technology infrastructure. With these steps, MI Nurul Hikmah can improve its competitiveness and adaptation to technological developments.